La aplicación de la prisión preventiva y el hacinamiento de los centros de rehabilitación social. - Yaulema Llangarí, Stalyn Iván (2023)
The current investigation is entitled "The application of preventive prison and the overcrowding of social rehabilitation centers." Preventive prison is a measure to ensure the appearance of people in the processes, where it delimits that this taken decision can upset a person both psychologically and physically; therefore, people sometimes need clarification on the application of justice for quick decisions. Its purpose is to determine the objectivity of preventive prison and its influence on overcrowding in social rehabilitation centers in Ecuador. Its design is a non-experimental documentary. Consequently, the type of research is descriptive and bibliographic. The data collection techniques were the survey and the instrument, the dichotomous questionnaire, used in a population of 24 professionals made up of principals of the social rehabilitation centers, supervisors of prison guides, the social rehabilitation centers of Ecuador with the highest incidence of prison crisis, judges of the Criminal Center and Public Defenders, allowing the adequate analysis for the elaboration of the research's conclusions and recommendations.